RETRACTED: miR-16 and Fluoxetine Both Reverse Autophagic and Apoptotic Change in Chronic Unpredictable Mild Stress Model Rats - Yang, Yang; Hu, Zhiying; Du, Xiaoxue; Davies, Henry; Huo, Xue; Fang, Marong (Frontiers in Neuroscience, 2017)
In the clinic selective serotonin reuptake inhibitors (SSRIs), like Fluoxetine, remain the primary treatment for major depression. It has been suggested that miR-16 regulates serotonin transporters (SERT) via raphe nuclei and hippocampal responses to antidepressants. However, the underlying mechanism and regulatory pathways are still obtuse. Here, a chronic unpredicted mild stress (CUMS) depression model in rats was established, and then raphe nuclei miR-16 and intragastric Fluoxetine injections were administered for a duration of three weeks. An open field test and sucrose preference quantification displayed a significant decrease in the CUMS groups when compare to the control groups, however these changes were attenuated by both miR-16 and Fluoxetine treatments. A dual-luciferase reporter assay system verified that hsa-miR-16 inhibitory effects involve the targeting of 3'UTR on the 5-HTT gene. Expression levels of miR-16 and BDNF in the hippocampus were examined with RT-PCR, and it was found that increased 5-HT2a receptor expression induced by CUMS can be decreased by miR-16 and Fluoxetine administration. Immunofluorescence showed that expression levels of neuron NeuN and MAP-2 in CUMS rats were lower. Apoptosis and autophagy levels were evaluated separately through relative expression of Bcl-2, Caspase-3, Beclin-1 and LC3II. Furthermore, CUMS was found to decrease levels of hippocampal mTOR, PI3K and AKT. These findings indicate that apoptosis and autophagy related pathways could be involved in the effectiveness of antidepressants, in which miR-16 participates in the regulation of, and is likely to help integrate rapid therapeutic strategies to alleviate depression clinically. These findings indicate that miR-16 participates in the regulation of apoptosis and autophagy and could account for some part of the therapeutic effect of SSRIs. This discovery has the potential to further the understanding of SSRIs and accelerate the development of new treatments for depression.